Learning-by-Doing Approach to Teach Microcontroller Course with Portable Training Board - Lu, Xueping; Ma, Yan; Fang, Yiming (International Journal of Emerging Technologies in Learning (iJET), 2023)
Microcontroller education is attracting increasing attention owing to the widespread application of microcontroller-based systems. This study proposes the learning-by-doing approach. Rather than emphasizing a deep understanding of datasheets and register-level programming, the new teaching model focuses on microcontroller-based applications. During the pre-class, in-class, and post-class phases, students were instructed to practice writing subroutines or building circuits to interface external devices with a training board. A typical case study is presented to illustrate the detailed process of the proposed model. Feedback from students and teaching supervisors in the recent years has shown that the teaching approach coupled with the training board provides students with more opportunities to work on real equipment, which benefits both the grasp of the theoretical knowledge and improvement of practical skills.